간호사의 임상판단 측정도구 개발 - 권시내; 박효정; Kwon, Shi Nae; Park, Hyojung (Journal of Korean Academy of Nursing, 2023)
Purpose: This study aimed to develop a nursing clinical judgment scale (NCJS) and verify its validity and reliability in assessing the clinical judgment of nurses. Methods: A preliminary instrument of the NCJS comprising 38 items was first developed from attributes and indicators derived from a literature review and an in-depth/focus interview with 12 clinical nurses. The preliminary tool was finalized after 7 experts conducted a content validity test based on a data from a preliminary survey of 30 hospital nurses in Korea. Data were collected from 443 ward, intensive care unit, emergency room nurses who voluntarily participated in the survey through offline and online for the verification of the construct validity and reliability of the scale. Results: The final scale comprised 23 items scored on a 5-point Likert scale. Six factors - integrated data analysis, evaluation and reflection on interventions, evidence on interventions, collaboration among health professionals, patient-centered nursing, and collaboration among nurse colleagues - accounted for 64.9% of the total variance. Confirmatory factor analysis supported the fit of the measurement model, comprising six factors (root mean square error of approximation = .07, standardized root mean square residual = .04, comparative fit index = .90). Cronbach's α for all the items was .92. Conclusion: The NCJS is a valid and reliable tool that fully reflects the characteristics of clinical practice, and it can be used effectively to evaluate the clinical judgment of Korean nurses. Future research should reflect the variables influencing clinical judgment and develop an action plan to improve it.